Synthesis of Various Heterocycles Having a Dienamide Moiety by Ring-Closing Metathesis of Ene-ynamides - Wakamatsu, Hideaki; Sasaki, Yoshimi; Kawahata, Masatoshi; Yamaguchi, Kentaro; Yoshimura, Yuichi (Synthesis, 2018)
Ring-closing metathesis (RCM) of ynamides, having alkene substituents of various lengths on the side chain, was demonstrated using the second-generation Grubbs catalyst. When the reaction of ene-ynamides was carried out in the presence of 5 mol% of the catalyst, RCM proceeded smoothly to give quinoline or isoquinoline derivatives having a dienamide unit in good yields. Furthermore, RCM of ene-ynamides, having one more carbon on the side chain, proceeded smoothly to provide seven-membered heterocycles having a dienamide component. Similarly, eight-membered heterocycles, diazocine and benzodiazocine, were also synthesized by RCM of ene-ynamides in good yields.
Keywords: ruthenium carbene complex; ynamide; ring-closing metathesis; heterocycles; medium-sized ring